The state : theories and issues - Hay, Colin, 1968-; Lister, Michael, 1976-; Marsh, David, 1946- (London ; New York : Bloomsbury Publishing Plc, 2022)
"With wide-ranging coverage and a contemporary outlook, this new edition introduces all of the main competing theoretical approaches to the study of the state, including pluralism, Marxism, institutionalism, feminism, green theory and more. A brand new 'issues' section then enables readers to apply these key concepts and theoretical approaches to important developments in the state today. Written by a team of experts in the field, this new edition offers: - A comprehensive account of key theories and issues, giving readers a solid understanding of state theory and its application - Coverage of all key empirical and theoretical developments in the field, with analysis of the impact of globalization, global financial upheavals, Brexit, Covid-19 and social movements such as Black Lives Matter - A wide range of voices, perspectives, contemporary and historical examples, giving readers a holistic overview of the field, as well as deeper dives into key issues - Brand new chapters on a range of topics, including: nationalism; populism; business - Guided further reading suggestions at the end of each chapter, recommending and explaining the significance of both seminal and cutting-edge texts. Providing both a firm grounding in the key concepts and critical engagement with contemporary controversies and debates, this text is perfect for those studying all aspects of the state"--
Introduction / Colin Hay & Michael Lister -- Part 1. Theories. Pluralism -- Elitism -- Marxism -- Public Choice -- Institutionalism -- Feminism -- Green Theory -- Poststructuralism -- Part 2. Issues. The State and Sovereignty -- The State and Security -- The State and Territory -- The State and Capital -- The State and Nationalism -- The State and Populism -- Conclusion / Michael Lister & David Marsh.
"First published in Great Britain 2005"--T.p. verso.
Includes bibliographical references and index.
Keywords: State, The; State, The -- History -- 20th century; Print books